Efektifitas Perbandingan Kombinasi Clindamycin dan Ekstrak Nannochloropsis Oculata Terhadap Peningkatan Kepadatan Kolagen pada Osteomielitis Mandibula - Faidha Azmi N; Dian Mulawarmanti; Noengki Prameswari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Osteomyelitis is an bone infection caused by bacteria of Staphylococcus aureus. The use of clindamycin within long term may cause of resistance. A compound in Nannochloropsis oculata’s extract contain antibacterial, antiinflamation, antioxidant that can be used as therapy of osteomyielitis. Purpose: Knowing comparison of the effectiveness between the combination of clindamycin and Nannochloropsis oculata’s extract to increasing the density of collagen on the mandibular osteomyelitis. Materials and Methods: The experimental research’s type with a design post test only control group. Fourty male wistar rats as model of mandibular osteomyelitis has made by inducing bacteria of Staphylococcus aureus inserted in socket after an extraction of left incisive teeth on lower jaw and waiting for 28 days. The rats are divided into 5 group: negative control (K1), clindamycin (K2),clindamycin with 50mg Nannochloropsis oculata’s extract (K3), clindamycin with 100mg Nannochloropsis oculata’s extract (K4), clindamycin with 200mg Nannochloropsis oculata’s extract. After 7 days, all of group are euthanazed and then the density of collagen measured using histopathology slide used Masson’s Trichom and 100x enlargement, so then analyzing the density of collagen by Kruskal-Wallis and Mann-Whitney. Result: There were significant differences in collagen between K1 and K2 (p=0,037), K1 and K3 (p=0,013), K1 and K4 (p=0,002), K1 and K5 (p=0,000). and there were significant differences in collagen between K2 and K5 (p=0,013). But there were no significant differences in collagen between group K2 and K3 (p=1,000), K2 and K4 (p=0,288). Conclusion: The combination of clindamycin with 200mg Nannochloropsis oculata’s extract having an effect on increasing number of the density of collagen significantly on the healing of mandibular osteomyelitis.